Prevalence of Carbapenem-Resistant Enterobacteriaceae Isolated from Clinical Samples in Medical Tobruk Center (Razi Medical Journal, 2025)
Globally, intensive care units (ICUs) are encountering the emergence and spread of antibiotic-resistant pathogens, and for some pathogens, there are few therapeutic options available. This study tries to assess the prevalence, susceptibility pattern, and risk factors of Carbapenem-Resistant Enterobacteriaceae (CRE) infections among ICU patients, healthcare workers, and surface swabs in the medical center of Tobruk, Libya. Also, to assess the incidence and prevalence rate of CRE in the medical center of Tobruk. A descriptive cross-sectional study was used to study 119 collected samples. Of which, 119 samples were collected from patients. The above samples were collected from four units of intensive care were intensive care unit (ICU) and cardiac care unit (CCU), Pediatric intensive care unit (PICU), Neonatal intensive care unit (NICU). The identified Enterobacteriaceae were first confirmed by biochemical methods, while the confirmed isolates were tested for carbapenemase production using three discs (EME, IMP, and ETP). The resistance to (Ertapenem, Imipenem, and Meropenem) was considered as CRE.  A total of 79 (66.4%) out of the 119 samples yielded clinical isolates of Enterobacteriaceae and gram negative bacteria from patients as follows:  23 (29.1%) Klebsiella pneumoniae, 15 (19%) Acinetobacter baumannii, 12 (15.2%) Escherichia coli, 7 (9%) Pantoea sp., 5 (6.3%) Pseudomonas aeruginosa, 5 (6.3%) Citrobacter freundii, 4 (5.1%) Enterobacter cloacae, 2 (2.6%) Citrobacter freundii, 3 (3.8%) Chryseomonas luteola, 2 (2.5%) Proteus vulgaris, 2 (2.5%)  Flavimonas oriyzihabitans, and 1 (1.3%) Serratia marcecens. Screening the Enterobacteriaceae-positive samples for carbapenem resistance showed 48 samples of 79 (60.8%) as carbapenem resistant Enterobacteriaceae as follows: 18 (22.8%) Klebsiella pneumonia, 9 (11.4%) Acinetobacter baumannii, 6 (7.6%) Escherichia coli, 4 (5.1%) Citrobacter freundii, 3 (3.8%) Pseudomonas aeruginosa, 3 (3.8%) Pantoea sp., 2 (2.5%) Enterobacter cloacae, 2 (2.5%) Chryseomonas luteola, 1 (1.3%) Serratia marcecens. The study provided evidence of the presence of CRE infections among patients admitted to ICUs in the study centers. This underscores the need for effective infection prevention and control measures to avoid the spread of CRE in a hospital setting.
Keywords: ICUs, Enterobacteriaceae, CRE, Gram negative bacteria , Antibiotic resistance